Uso de cupinzeiros terrícolasterrestres para nidificação de aves em duas áreas antropizadas do Estado de São Paulo - Santos, André Cid Fernandes Arruda (2017)
Several sites that have been altered by anthropic activities may serve as habitats of animal species; areas of pasture between fragments present some resources such as food and shelter. An important resource used by animals of various classes are termite mounds and their cavities excavated mainly by birds, such as woodpeckers. The use of cavities by birds in termites is still poorly studied, although this can contribute to the conservation and maintenance of bird populations dependent on these structures. The objective of this study was to analyze and to monitor the use of bird cavities in termites in pasture areas with different intensities of use and to identify the possible selectivity of specific characteristics of these structures as sites for nests construction. In total, 1801 termite mounds were found and analyzed, seven of which were used by the burrowing owl, Athene cunicularia, and six by the campo flicker, Colaptes campestris. As a secondary use, a single nest of C. campestris was used by the owl Megascops choliba. None of the species presented selectivity regarding to the height and width of termites used to construct the nests. The proportion of termites used by A. cunicularia did not differ between areas, but C. campestris showed a significant preference for an area without the presence of cattle. As a main recommendation, it is indicated that in the management of termite mounds in pasturelands, those with existing cavities should be maintained to guarantee the secondary use.